Problems of High Technology Production in Lithuania - Vilkas, Eduardas (Ekonomika, 2002)
Development of high technology production is one of the key factors in long term development strategy of Lithuania’s economy. Problems of choosing priorities and measures in high technology development are studied. European experience in the field is utilised for carrying out Lithuanian high-tech programme. The programme describes the following priority areas: biotechnology, mechatronics, laser technologies and informational technologies. Criteria used to choose these priorities are as follows: sufficient scientific human capital of world level quality, existence of production competitive in world market, prospects of further technology development, in particular, being in agreement with EU technology priorities, possibility to find a niche in world market safe from large international companies competition, a relatively low need for human and financial inputs. The main goal of the programme is to develop human capital and research aiming to create the new high-tech products and to improve respective entrepreneur capacities for commercialisation of new technologies.